Solar PV Penetration Scenarios for a University Campus in KSA - Sager Alsulamy (Energies, 2022)
The Kingdom of Saudi Arabia (KSA) is committed to transition its fossil fuel-driven electricity generation to that from renewable energy technologies, such as solar photovoltaic (PV) and wind. The need to reduce greenhouse gas emissions has led it to announce an ambitious target of 40 GW of PV power capacity by 2030. The deployment of such a capacity needs to be augmented with analyses to overcome the challenges faced in terms of the technical capability of the country. This work contributes to this goal by investigating the utilisation of solar photovoltaic PV systems to supply medium-size entities such as universities with clean power, displacing the current fossil fuel power supply. Currently, such considerations are not fully addressed in KSA. The study used the University of Jeddah campus electrical load profile, taking into account future power needs. The methodology encompassed modelling the installation of multi-MW PV systems for the university by considering weather conditions, actual university consumption, load segregation, and economics under different development scenarios informed by surveys with decision makers at the university. The results showed that air conditioning loads alone were responsible for 79% of the campus electrical load and that a 4.5 MW PV system is able to supply half of the total campus annual electrical energy consumption of the year of 2019. The optimum scenario showed that utilising grid-connected PVs would decrease the total cost of electricity over the next two decades by 28 to 35 percent and would result in halving the current campus carbon emissions. The analysis concludes that the business-as-usual case is no longer the cheapest option for the campus.